Pencirian sifat komposit polimer bergentian semula jadi untuk aplikasi struktur - Liew, Shan Chin (2008)
Oil palm fibre which is relatively low cost and abundantly available has the potential as polymer reinforcement in structural applications. This study initially investigated the tensile behaviour of single oil palm fibre and physical properties like diameter, moisture content, moisture absorption and density. Then, the tensile behaviour of natural fibre reinforced polymer composites as a function of fibre volume ratio, fibre length and fibre surface modification was investigated. Lastly, flexural behaviour of reinforced concrete beam strengthened with unidirectional oil palm fibre composite was tested and was compared with reinforced concrete beam strengthened with woven glass fibre composite and ordinary reinforced concrete beam. Oil palm fibre is light but high moisture content, high moisture absorption and large variance of cross section area. The fibre tensile properties are relatively low compare to the literature which may due to degradation problems. The stiffness of the composite is significantly improved when the fibre volume ratio increased. At 10% of fibre volume ratio, the modulus of elasticity is increased up to 150 % compare to neat resin. Higher aspect ratio yield higher tensile strength and modulus of elasticity of the composite. The effect of alkali treatment increases 10% of the tensile strength of the fibres. Oil palm fibre composite could be used as strengthening material for reinforced concrete beam by increasing the flexural strength and stiffness of the reinforced concrete beam while maintaining the ductility of the beams.